2003
DOI: 10.1038/sj.bmt.1703860
|View full text |Cite
|
Sign up to set email alerts
|

Successful mobilization of peripheral blood stem cells after addition of ancestim (stem cell factor) in patients who had failed a prior mobilization with filgrastim (granulocyte colony-stimulating factor) alone or with chemotherapy plus filgrastim

Abstract: Summary:This study assessed the ability of recombinant human stem cell factor (rHuSCF) to mobilize stem cells in 44 patients who had failed a prior mobilization (CD34 + yield 0.5-1.9 Â 10 6 /kg BW) with filgrastim-alone or chemotherapyplus-filgrastim. The same mobilization regimen was used with the addition of rHuSCF. In the filgrastim-alone group (n ¼ 13), rHuSCF 20 lg/kg was started 3 days before filgrastim and continued for the duration of filgrastim. In the chemotherapy-plus-filgrastim group (n ¼ 31), rHuS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
(14 reference statements)
2
33
0
Order By: Relevance
“…107 However, subsequent reports indicated that SCF may have a role in the treatment of patients with lymphoma and other malignancies who have undergone multiple rounds of intensive chemotherapy. 108,109 Stiff et al 108 reported that a combination of G-CSF 10 mg/kg s.c. and SCF 20 mg/kg s.c. administered daily for 5-9 days resulted in significantly higher CD34 þ cell yields (3.6 Â 10 6 /kg) than did treatment with G-CSF alone (2.4 Â 10 6 /kg; P ¼ 0.05) in a randomized trial of 102 heavily pretreated patients who had NHL or HD. 108 Dawson et al 110 studied remobilization after X5 daily doses of SCF 20 mg/kg plus twice daily administration of G-CSF 10 mg/ kg, with or without CY, in 48 patients who had been heavily pretreated for a hematological malignancy and in whom a previous mobilization with G-CSF alone or with chemotherapy had failed.…”
Section: Scfmentioning
confidence: 99%
“…107 However, subsequent reports indicated that SCF may have a role in the treatment of patients with lymphoma and other malignancies who have undergone multiple rounds of intensive chemotherapy. 108,109 Stiff et al 108 reported that a combination of G-CSF 10 mg/kg s.c. and SCF 20 mg/kg s.c. administered daily for 5-9 days resulted in significantly higher CD34 þ cell yields (3.6 Â 10 6 /kg) than did treatment with G-CSF alone (2.4 Â 10 6 /kg; P ¼ 0.05) in a randomized trial of 102 heavily pretreated patients who had NHL or HD. 108 Dawson et al 110 studied remobilization after X5 daily doses of SCF 20 mg/kg plus twice daily administration of G-CSF 10 mg/ kg, with or without CY, in 48 patients who had been heavily pretreated for a hematological malignancy and in whom a previous mobilization with G-CSF alone or with chemotherapy had failed.…”
Section: Scfmentioning
confidence: 99%
“…27,49,50 Mobilization could also be induced within hours after administration of certain chemokines (for example, interleukin-8, growth-related oncogene protein-beta (Gro-b) or macrophage inhibitory protein-1a), multiple injection of certain growth factors (for example, Fms-like tyrosine kinase 3, kit ligand or vascular endothelial growth factor), small-molecule antagonists of the CXCR4 receptor (for example, AMD3100 or T139) or a small-molecule antagonist of VLA-4 (BIO4860). [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] To obtain more efficient and faster mobilization, some of these compounds could be administered together (for example, G-CSF with AMD3100 or growth-related oncogene protein-beta with AMD3100). 28,61 Mobilization could also be achieved by the administration of some types of polysaccharides (for example, zymosan or fucoidans) that in animal models have been demonstrated to efficiently mobilize HSPCs within 1 h after a single injection.…”
Section: Pharmacological Mobilization Of Hspcsmentioning
confidence: 99%
“…[1][2][3][4] PBCD34 reflects the extent of mobilization of stem cells from the bone marrow into the blood-and depends upon a number of factors including diagnosis, extent of prior therapy, mobilization technique and type and dose of the growth factor used. 3,[5][6][7][8][9] However, PBCD34 is not always immediately available at the planned time of apheresis. Waiting for a PBCD34 result for a few hours may result in a delayed start or even a missed opportunity for a good stem cell collection.…”
Section: Introductionmentioning
confidence: 99%